A Framework for Evaluation of TESOL Programs - Alkin, Marvin C.; Woolley, Dale C.; California Univ., Los Angeles. Center for the Study of Evaluation ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
The authors present a framework depicting an evaluation-decision sequence, describe each of the evaluation stages, and note the relationships between evaluation information and subsequent decisions. In Chart I, the four major decision areas and the five kinds of evaluation which provide information for decisions in each of these areas are identified. It is hoped that this model for educational evaluation points out the importance of evaluation information in the process of improving educational programs and helping to ensure their success. The authors emphasize that evaluation should begin when an educational agency first looks critically at the potential of the educational process in its particular system and not after all attempts at improvement have been concluded. (Authors/AMM)
Contract Number: OEC-4-6-061646-1909.
ERIC Note: Paper given at the fourth annual TESOL Convention, San Francisco, California, March 18-21, 1970.
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Bureau of Research.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Instructional Improvement; Educational Development; English (Second Language); Instructional Programs; Program Evaluation